Pengaruh Gaya Kepemimpinan dan Budaya Organisasi Terhadap Kinerja Karyawan dengan Kepuasan Kerja Sebagai Variabel Intervening Pada PT. Kilang Lima Gunung Kota Padang - Adis Putra Syahditia; Vicky Brama Kumbara; Nia Nadilla (Jurnal Ekonomi dan Bisnis Digital, 2026)
This study aims to determine and analyze the influence of leadership style and organizational culture on employee performance, with job satisfaction serving as an intervening variable at PT. Kilang Lima Gunung, Padang City. This research employs a Structural Equation Modeling (SEM) approach using SmartPLS 3.0 as the analytical tool. The population and sample of this study consisted of 57 employees of PT. Kilang Lima Gunung, Padang City. Data were collected through the distribution of questionnaires directly to employees who worked at the company. The results of the study indicate that leadership style has a positive but insignificant effect on job satisfaction. Organizational culture has a positive and significant effect on job satisfaction. Leadership style has a positive but insignificant effect on employee performance. Organizational culture has a positive and significant effect on employee performance. Job satisfaction has a negative and insignificant effect on employee performance. Furthermore, job satisfaction does not mediate the relationship between leadership style and employee performance. Likewise, job satisfaction does not mediate the relationship between organizational culture and employee performance.